Bisnis Susu Sapi Perah Perspektif Hukum Ekonomi Syariah di Kabupaten Banyuwangi - Moh. Khafiluddin (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
The Ijen Makmur Dairy Farming Group was a group that was founded in July 2014 so it was fairly new in Tamansari Village. The type of research used in this research was descriptive qualitative research, while the data sources were obtained through observation, interviews, and documentation. The data were analyzed descriptively through reduction, display and verification (conclusion). The collaboration of the Ijen Dairy Cattle Breeders Group was a type of syirkah al-inan, because each member of the group contributes capital and works with agreed wages or profit-sharing. Meanwhile, in terms of distribution of dairy cow's milk, the Ijen Makmur Dairy Farmers Group had two types of market share, namely the fixed market and the local or non-fixed market. The income from milk production that had been deposited by the farmers to the company was distributed equally or calculated equally among members after previously deducting operational costs.